Method of Calculating Life-Cycle Fatigue Damage of Orthotropic Steel Bridge Decks under the Combined Actions of Vehicle Loads and Pavement Temperature - Gaoxin Wang; Youliang Ding; Zhijun Liu; Jingshu Shao (Shock and Vibration)
The fatigue analysis on orthotropic steel bridge decks is a hot topic in bridge engineering field. This study provides one method for fatigue analysis under the combined actions of vehicle loads and pavement temperature. To be specific, taking the steel bridge deck of one cable-stayed bridge as a research object, this study proposes a method of calculating life-cycle fatigue damage of orthotropic steel deck under the combined actions of vehicle loads and pavement temperature. First, a finite element model of steel bridge deck with asphalt pavement is built to analyze the influence of pavement temperature on the fatigue stress of steel bridge deck. Second, a simulation method of fatigue stress caused by random vehicle loads is proposed. Finally, a method of calculating the life-cycle fatigue damage of welded joints under the combined actions of vehicle loads and temperature is proposed. The results show that temperature has a significant effect on fatigue damage, and the cumulative fatigue damage in the rib-to-rib welded joint is significantly greater than that in the deck-to-rib welded joint. The results can provide meaningful references for bridge engineers to carry out fatigue analysis on orthotropic steel bridge decks.